1998
DOI: 10.1016/s0009-9236(98)90021-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a human thiopurine S-methyltransferase (TPMT) complementary DNA with a single nucleotide transition A719G (TPMT*3C) and its association with loss of TPMT protein and catalytic activity in humans*

Abstract: These data establish that the TPMT*3C allele is expressed in humans and is associated with lower immunodetectable TPMT protein and catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 12 publications
0
40
0
Order By: Relevance
“…Second explanation maybe the relatively low dose of AZAadministration in Japan (commonly 1 mg/kg/day), compared to the dose commonlyprescribed for the treatment of rheumatoid arthritis in Caucasians (2-3 mg/kg/day). However, recently it was reported that erythrocytes obtained from patients with TPMT*3AfTPMT*3C genotype showed no TPMT function and patients with TPMT*1/TPMT*3C showed intermediate TPMTactivity, indicating that TPMT*3Callele is nonfunctional in vivo (6), and when expressed in humans, TPMT*3Cis likely associated with lower TPMTprotein levels and catalytic activity in erythrocytes (13). Considering these, the second explanation, that the relatively low dose of AZA administration in Japan is the reason for the mildness of side effects, is considered to be more plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Second explanation maybe the relatively low dose of AZAadministration in Japan (commonly 1 mg/kg/day), compared to the dose commonlyprescribed for the treatment of rheumatoid arthritis in Caucasians (2-3 mg/kg/day). However, recently it was reported that erythrocytes obtained from patients with TPMT*3AfTPMT*3C genotype showed no TPMT function and patients with TPMT*1/TPMT*3C showed intermediate TPMTactivity, indicating that TPMT*3Callele is nonfunctional in vivo (6), and when expressed in humans, TPMT*3Cis likely associated with lower TPMTprotein levels and catalytic activity in erythrocytes (13). Considering these, the second explanation, that the relatively low dose of AZA administration in Japan is the reason for the mildness of side effects, is considered to be more plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the homozygous deficiency in humans is characterized by almost undetectable levels of TPMT protein; heterozygotes have intermediate protein and activity levels; and homozygous wild-type individuals have high levels of protein and activity (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…For example, mean erythrocyte TPMT activity in African subjects was 20% percent lower that in Caucasians from the same location [4]. Based on the population phenotype-genotype studies performed to date, assays for the molecular diagnosis of TPMT deficiency have focused on TPMT * 2 (G238C) [8], TPMT * 3A (G460A/A719G) [9], and TPMT * 3C (A719G) [10]. These three mutant alleles account for the majority of low activity alleles in human populations studied to date [11].…”
Section: Introductionmentioning
confidence: 99%